2012
DOI: 10.1007/s00592-012-0443-9
|View full text |Cite
|
Sign up to set email alerts
|

PPARG2 Pro12Ala and ADAMTS9 rs4607103 as “insulin resistance loci” and “insulin secretion loci” in Italian individuals. The GENFIEV study and the Verona Newly Diagnosed Type 2 Diabetes Study (VNDS) 4

Abstract: We investigated cross-sectionally whether the type 2 diabetes (T2DM) risk alleles of rs1801282 (PPARG2) and rs4607103 (ADAMTS9) were associated with T2DM and/or insulin sensitivity (IS) and beta cell function (βF) in Italians without and with newly diagnosed T2DM. In 676 nondiabetic subjects (336 NGR and 340 IGR) from the GENFIEV study and in 597 patients from the Verona Newly Diagnosed Type 2 Diabetes Study (VNDS), we (1) genotyped rs1801282 and rs4607103, (2) assessed βF by C-peptide/glucose modeling after O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…For those few biomarkers for which the Mendelian randomisation approach has been used, the majority (adiponectin [23,24], C-reactive protein [25], Fetuin-a [26], triglycerides [27], vitamin D [28,29], IL-1Ra [30] and uric acid [31]) have evidence that is consistent with the biomarker not being causally related to T2D risk. The rest of the biomarkers, including those related to beta-cell function [32,33], HOMA-IR [33], ferritin (Transmembrane protease serine 6)[34], homocysteine [35], N-terminal pro B-type natriuretic peptide (NT-proBNP)[36], bilirubin [37] and resistin [38] were claimed to be causally associated with T2D (S5 Table). …”
Section: Resultsmentioning
confidence: 99%
“…For those few biomarkers for which the Mendelian randomisation approach has been used, the majority (adiponectin [23,24], C-reactive protein [25], Fetuin-a [26], triglycerides [27], vitamin D [28,29], IL-1Ra [30] and uric acid [31]) have evidence that is consistent with the biomarker not being causally related to T2D risk. The rest of the biomarkers, including those related to beta-cell function [32,33], HOMA-IR [33], ferritin (Transmembrane protease serine 6)[34], homocysteine [35], N-terminal pro B-type natriuretic peptide (NT-proBNP)[36], bilirubin [37] and resistin [38] were claimed to be causally associated with T2D (S5 Table). …”
Section: Resultsmentioning
confidence: 99%
“…The genetic variations underlying the link between lipids parameters and cardiometabolic traits have been analyzed by various studies but remain unclear. PPARG2 rs1801282 polymorphism has been associated with impaired insulin sensitivity and was called indeed “insulin resistance locus” [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Although individuals carrying the Gly972Arg are reported to have a 25% increased risk for developing diabetes [10], genome wide association (GWAS) studies involving subjects of European descent found no association between IRS1 and type 2 diabetes [26,27]. On the other hand, the PPARG Pro12Ala, particularly the 12Ala has been associated with a reduced risk of type 2 diabetes and insulin resistance [9,16-20]. As such, the polymorphisms of the IRS1 and PPARG genes have been shown to interact and elevate insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several variants in the PPARG gene have been identified, with the most prevalent variant being the Pro12Ala polymorphism resulting from the CCA-to-GCA missense mutation in codon 12 of exon B that encodes the NH 2 terminal residue [13-15]. The proline which is the common allele is associated with increased risk whilst the alanine confers a protective effect against insulin resistance and type 2 diabetes [9,16-20]. In contrast, the glycine to arginine substitution in codon 972 (Gly972Arg) of the IRS1 gene is associated with an increased risk of insulin resistance [21].…”
Section: Introductionmentioning
confidence: 99%